2019
DOI: 10.1590/0037-8682-0499-2018
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antibiotic resistance genes and virulence factors in Escherichia coli isolated from Turkish patients with urinary tract infection

Abstract: Introduction: Escherichia coli ranks among the most common sources of urinary tract infections (UTI). Methods: Between November 2015 and August 2016, 90 isolates of E. coli were isolated from patients at Rize Education and Research Hospital in Turkey. Antibiotic susceptibility was determined for all isolates using the Kirby-Bauer disk diffusion method. These E. coli isolates were also screened for virulence genes, β-lactamase coding genes, quinolone resistance genes, and class 1 integrons by PCR. Results: With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
4
8
5
Order By: Relevance
“…This will serve as a means or a strategy for survival in all conditions the organisms may find themselves. Rahdar et al (2015), and Duzgun et al (2019), also reported similar results in their studies [36,37]. Of the other genes for adhesion, papC was found to be relatively higher than sfaS.…”
Section: Discussionsupporting
confidence: 59%
“…This will serve as a means or a strategy for survival in all conditions the organisms may find themselves. Rahdar et al (2015), and Duzgun et al (2019), also reported similar results in their studies [36,37]. Of the other genes for adhesion, papC was found to be relatively higher than sfaS.…”
Section: Discussionsupporting
confidence: 59%
“…Key virulence factors involved in the pathophysiology of UTIs function in invasion, colonization and mediation of host defences subversion [ 8 ]. PAIs furthermore often carry cryptic or functional genes that encode mobility factors, such as integrases, transposases and insertion sequence elements [ 7 ], which are traces from their mobile history and may promote and contribute to the spread and emergence of antimicrobial resistance [ 9 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, there have been a few studies featuring virulence properties, antibiotic resistance, and its relationship with phylogenetic groups among E. coli associated with UTIs in Turkey [10][11][12][13] . Therefore, the main objective of this study was to determine the antimicrobial susceptibility, phylogeny, and virulence genes of E. coli isolated from patients admitted to Hatay State Hospital with UTI complaint.…”
Section: Introductionmentioning
confidence: 99%